Fabrication and characterisation of ceramic-polymer composites for orthodontic brackets - Cheong, Joo Ming; Su, B.; Sandy, J. R; Ireland, A.J (2017)
Objectives: To produce a ceramic-polymer composite for possible use as an aesthetic orthodontic bracket material.